Effects of age at fattening on male Butana camels performance and some blood parameters in the Sudan - Hamed, Asma; Elimam, Mohamed; Omer, Solafa; Ombabi, Yassir (Gezira Journal of Agricultural Science; Vol 12 No 2 (2014), 2014)
Twelve male Butana camels at 2,3 and 4 years old (four in each age group) were  fattened for two month in Gadarif, Gadarif State, Sudan to study the effects of age at fattening on animals performance and some haematological factors. They were weighed at the beginning of the experiment and then weekly. Each animal was fed sorghum stover ad lib in two equal meals in the morning and afternoon and 2.0 kg concentrates daily. Clean drinking water was offered ad lib . Feeds DM digestibility was measured for seven days in the last week of the experiment. Jugular vein blood samples were collected for determination of some blood parameters. Daily sorghum stover DMI, TDMI and water intake (litres/day) increased with age at fattening and were higher at 4 years old. Dry matter digestibility increased with age at fattening and was highest at 4 years old. Initial and final body weights and mean daily and weekly weight gains increased with age at fattening. Total weight gain increased up to 3 years and then decreased and was affected with age, except between 2 and 4 years old. Feed conversion ratio was highest at 4 years old. Leucocytes count increased with age at fattening and varied between 2 and 4 years old. Red blood cells count, haemoglobin and packed cell volume increased up to three years old and then decreased. Red blood cells count and haemoglobin varied between 2 and 3 years old.       تم تسمين 12 من ذكور أبل البطانة  بأعمار 2، 3 و4 سنوات(أربعة في كل مجموعة عمرية) لمدة شهرين في القضارف بولاية القضارف في السودان لدراسة أثر عمر التسمين على الأداء وبعض صفات الدم. وزنت الحيوانات عند بدء التجربة ثم أسبوعياً. أعلف كل حيوان يومياً تبن الذرة الرفيعة حسب الرغبة في وجبتين متساويتين صباحاً وبعد الظهر و2 كجم عليقة مركزة وقدم ماء نظيفاً حسب الرغبة. نم فياس هضمية المادة الجافة لمدة سبعة أيام في الأسبوع الأخير للتجربة. جمعت عينات دم من الوريد الودايجي لقياس بعض مكونات الدم.. زاد التبن المأكول والعلف الكلي  المأكول وماء الشرب (لتر) يومياً  بزيادة عمر التسمين وكانت أعلى بعمر 4 سنوات. زادت هضمية المادة الجافة بزيادة عمر التسمين وكانت اعلى بعمر4 سنوات. زاد الوزن المبدئي والنهائي  ومتوسط الوزن المكتسب اليومي والاسبوعي بزيادة عمر التسمين وكانت أقل بعمر عامين.  زاد الوزن المكتسب الكلي حتى عمر 3 سنوات ثم انخفض وتأثر بالعمر. إلا بين عامين وأربعة أعوام. كانت كفاءة تحويل العلف أعلى  بعمر 4 سنوات. زاد عدد كريات الدم البيضاء بعمر التسمين واختلف بين عمر عامين وأربعة اعوام. زاد عدد  كريات الدم الحمراء والهمقلوبين وحجم الخلايا المضغوطة حتى عمر3 سنوات ثم انخفض. تباين عدد كريات الدم الحمراء والهمقلوبين بين عمر عامين وثلاثة أعوام.